The ability of image postproduction to replace analogue cameras - Tanuilov, Maksim; Krauz, Tomáš; Krsek, Libor, 1979-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
The popularity of the desire to achieve a “film look” has been rising for a couple of years. The goal of the thesis is to develop a workflow that helps to emulate this look by using RAW files, a digital camera and Dehancer plugin. The thesis describes the characteristics of film stocks and RAW digital files that play a key role in the emulation process. To test the hy-pothesis that the post-production process could emulate the look of film stocks upon the condition of using specific software and workflow, an experiment has been conducted. Se-ries of digital and filo photographs have been shot in the studio lighting conditions. To re-ceive objective results, two same lenses and the same lighting scheme have been used for pictures. The results showed that the developed workflow can emulate the film look, howev-er, it did have some disadvantages caused by software limitations. The main problems in-clude working with colors and shadows. For example, during editing in the Color grading section, the midtones also affected the shadows of dark objects. Therefore, the dark objects in the digital photo did not match the dark objects in the analog photo. This suggests that film look can be emulated. On the other hand, a universal preset cannot be developed to suit all the lighting conditions and compositions
Vedoucí práce: Tomáš Krauz
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses